Motor adaptation and immediate retention to overground gait-slip perturbation training in people with chronic stroke: an experimental trial with a comparison group - Bhatt, Tanvi; Dusane, Shamali; Gangwani, Rachana; Wang, Shuaijie; Kannan, Lakshmi (Frontiers in Sports and Active Living, 2023)
Background: Perturbation-based training has shown to be effective in reducing fall-risk in people with chronic stroke (PwCS). However, most evidence comes from treadmill-based stance studies with a lack of studies training overground perturbed walking and also examining the relative contributions from the paretic and non-paretic limbs. This study thus examined whether PwCS could acquire motor adaptation and demonstrate immediate retention of fall-resisting skills following bilateral overground gait-slip perturbation training. Methods: 65 PwCS were randomly assigned to either i) a training group, that received blocks of eight non-paretic (NP-S1 to NP-S8) and paretic (P-S1 to P-S8) overground slips during walking followed by a mixed block (seven non-paretic and paretic slips each interspersed with unperturbed walking trials) (NP-S9/P-S9 to NP-S15/P-S15) or ii) a control group, that received a single non-paretic and paretic slip in random order. The assessor and training personnel were not blinded. Immediate retention was tested for the training group after a 30-minute rest break. Primary outcomes included laboratoryinduced slip outcomes (falls and balance loss) and center of mass (CoM) state stability.(p<0.01). Post-slip stability on the paretic slip was lower than that on the non-paretic slip for both groups on retention trials (p<0.01). Conclusion: PwCS can reduce laboratory-induced slip falls and backward balance loss outcomes by adapting their post-slip CoM state stability after bilateral overground gait-slip perturbation training. Such reactive adaptations were better acquired and retained post-training in PwCS especially on the non-paretic slips than paretic slips, suggesting a need for higher dosage for paretic slips.